Kosovo : Macroeconomic Issues and Fiscal Sustainability - Corker, Robert (International Monetary Fund, 2001)
Since the end of the conflict in Kosovo-a province of Serbia in the Federal Republic of Yugoslavia-in June1999, IMF staff have been providing technical assistance to help the province rebuild its economy. The assistance has focused on setting up taxation and budgetary institutions, a payments and banking system, and a statistical framework. The IMF staff has also provided general macroeconomic policy advice, especially on budget formulation, which is the main focus of this publication. The IMF's technical assistance has been carefully coordinated with that of the World Bank and donor agencies.